Spontaneous maturation of stage IV–S neuroblastoma. Issue 10 (October 1978) - Rangecroft, L; Lauder, I; Wagget, J
Abstract : A case of stage IV–S neuroblastoma is presented in which treatment has deliberately been kept to a minimum. Gradual maturation to ganglioneuroma has been documented and the patient's generally good progress has justified this approach.